Molecular aspects in inflammatory events of temporomandibular joint: Microarray-based identification of mediators. Issue 1 (February 2015) - Ogura, Naomi; Kondoh, Toshirou
Summary: Synovial inflammation (synovitis) frequently accompanies intracapsular pathologic conditions of the temporomandibular joint (TMJ) such as internal derangement (ID) and/or osteoarthritis (OA), and is suggested to be associated with symptom severity. To identify the putative factors associated with synovitis, we investigated interleukin (IL)-1β- and/or tumor necrosis factor (TNF)-α-responsive genes of fibroblast-like synoviocytes (FLS) from patients with ID and/or OA of TMJ using microarray analysis. In this review, we first summarize the FLS of TMJ and the signaling pathways of IL-1β and TNF-α. Next, we show the up-regulated genes in FLS after stimulation with IL-1β or TNF-α, and summarize the gene functions based on recent studies. Among the top 10 up-regulated factors, molecules such as IL-6 and cycrooxygense-2 have been well characterized and investigated in the inflammatory responses and tissue destruction associated with joint diseases such as RA and OA, but the roles of some molecules remain unclear. The FLS reaction can lead to the synthesis and release of a wide variety of inflammatory mediators. Some of these mediators are detected in joint tissues and synovial fluids under intracapsular pathologic conditions, and may represent potential targets for therapeutic interventions in ID and/or OA of TMJ.